Collective Health Nursing: desires and practices - Fortuna,Cinira Magali (2019)
ABSTRACT Objective: To discuss and reflect on collective health nursing practices, presenting the work-related experience of nurses. Method: This was a reflection paper based on the labor process theory. Results: Studies conducted in research groups, discussions at scientific events, and professional experiences point to the importance of recognizing the intentionality of health work. Furthermore, it is essential t understand the health-illness-care process adopted and advocated by health professionals, and the role of social determinants and the entire historical, political, economic and social context of professional training, healthcare service organization and society. Conclusion: Collective health nursing practices play an important role in the health care provided to the population. Nurses are reference professionals in health care in all stages of life; however, further reflection is required on professional training, politicization, and the concepts of health and illness that guide professional practices.